2022
DOI: 10.3390/foundations2030052
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Electromagnetic Radiation and the Acoustic Emission Response of Multi-Scale Rock-like Material Failure and Their Application

Abstract: In order to explore the evolution characteristics of multi−scale rock−like material failure, we studied the acoustic emission (AE) and electromagnetic radiation (EMR) characteristics of different scale rock−like materials by using the AE−EMR experimental system of coal and rock failure, and the AE and EMR response law of rockburst in mining sites was analyzed. The results show that under uniaxial loading, the stress–strain curve of the specimen has a compaction stage, linear elastic stage, elastic–plastic stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Fursa et al [ 96 ] focused on investigating the variations in acoustic and electromagnetic emission parameters, identifying high-amplitude AE and the appearance of EMR signals as primary diagnostic criteria for concrete cracking initiation. Li et al [ 97 ] observed that the cumulative EMR counts for concrete, and similar rock-like materials exhibit a decreasing-then-increasing trend with increasing stress levels during loading and unloading. The drastic change in EMR occurs only during collapse.…”
Section: Electromagnetic Radiation Monitoringmentioning
confidence: 99%
“…Fursa et al [ 96 ] focused on investigating the variations in acoustic and electromagnetic emission parameters, identifying high-amplitude AE and the appearance of EMR signals as primary diagnostic criteria for concrete cracking initiation. Li et al [ 97 ] observed that the cumulative EMR counts for concrete, and similar rock-like materials exhibit a decreasing-then-increasing trend with increasing stress levels during loading and unloading. The drastic change in EMR occurs only during collapse.…”
Section: Electromagnetic Radiation Monitoringmentioning
confidence: 99%
“…It is noteworthy that with the continuous extension of coal mining deeper underground, ground stress and gas pressure in coal seams gradually increase, and coal and gas outbursts, rock bursts, and other coal rock dynamic disasters become more serious and complex [24]. It is known that in the processing of rocks in the mines electromagnetic radiation occurs.…”
Section: The Additional Practical Use Of the Researchmentioning
confidence: 99%